Smart Home Security System Using IoT - Jausin, Frederick; Bakar, Lilywati; Abdul Wahab, Zurina (Progress in Engineering Application and Technology, 2022)
In this current era towards the development of technologies, a lot of electronic devices are wireless and a lot of industry has already towards industrial 4.0. the purpose of this Smart Home Alarm System Using IoT is to help people live a safe environment and making sure that the home has protection against unwanted guests such as intruders and to prevent or to help people from being caught in a fire. Nevertheless, current issues suggested the need of improving the security alarm so not only it can protect people but also help people to monitor their home wireless by only using their smartphones which can be monitored from every inch of the globe. This project can identify which location of the house is being intruded or where the fire started burning by using a sensor that will be placed at different zones, such as zone 1 and zone 2. The words zone here is just an indication which can be any names regarding where the sensor is placed such as in the living room or kitchen. When the sensors have triggered either fire or intruder, the device will read and send a notification to the owner via the Blynk application that is installed in their smartphone. Besides that, a camera will also be installed which can be used to monitor from distances using the specific application or browser. For the fire alarm, a notification will be sent to the mobile phone to warn the user that there is a fire, smoke or gas leak inside the house. For the Intruder alarm, a buzzer will not be installed but it can be applied also. The reason why the intruder alarm is not installed with a buzzer is to make sure that a panic situation will not be created, to prevent other people from getting hurt by the intruders, and intruders can be cunningly detained by authorities.